VALIDATION OF ETHNOPHARMACOLOGICAL USE AS ANTI-INFLAMMATORY OF A DECOCTION FROM ANNONA MURICATA LEAVES - Quilez, A. M.; la Paz, S. Montserrat-de; Puerta, R. De la; Fernández-Arche, M. A.; GarcÃa-Giménez, M. D. (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Through this work we evaluated the potential of the aqueous extract of Annona muricata L. leaves (AMAEL) to treat inflammatory conditions. The use of decoction or infusion of this important medicinal resource is still not scientifically validated. Methods: Different doses of AMAEL were assayed in carrageenan-induced inflammation and tetradecanoylphorbol acetate (TPA)-induced edema in mice, myeloperoxidase activity (MPO) in inflamed tissue, MPO released by A-23187-stimulated rat neutrophils and nitric oxide released by murine macrophages. Acute oral toxicity and cell viability of murine macrophages were also tested. Results: A single dose of 250, 500 and 1000 mg/kg of AMAEL did not show any symptoms associated with toxicity in vivo and the viability of murine macrophages was of 100% at the assayed doses. AMAEL at 250mg/kg and 500mg/kg exerted a significant edema reduction in the carrageenan inflammation model (26.82±0.02%, p<0.05 and 52.70±0.12%, p<0.001 inhibition respectively, after the first hour). The TPA-induced topical edema model showed a significantly and dose-dependently inhibition (56% and 78% at doses of 2.5 mg/ear and 5 mg/ear, respectively). The decrease in (MPO) enzyme activity in the ear homogenates assayed at 5 mg/ear were highly significant (92.5% ± 1.83 inhibition, p<0.001) and MPO was also reduced in activated rat neutrophils at 200 µg/ml (81.98% ± 1.01 inhibition, p<0.001). AMAEL considerably decreased dose-dependently nitrite production in LPS-stimulated murine macrophages, the highest inhibition was achieved at 500 µg/ml (73.18% ± 2.36, p<001). Conclusion: this study validates the ethnomedicinal use of the decoction of Annona muricata L. leaves as anti-inflammatory agent